Plan de negocios para el Laboratorio de Biotecnología de Plantas y el Laboratorio de Fisiología Vegetal del TEC Campus Tecnológico Local San Carlos - Araya-Fernández, Natalia; Barrantes-Cortes, Jonathan (Instituto Tecnológico de Costa Rica, 2018)
This document shows a Business Plan for the Plant Biotechnology Laboratory and the Plant Physiology Laboratory of Technological of Costa Rica, San Carlos Local Technological Campus. To carry out the study, the research was through a mixed-type approach with descriptive scope, on the sector in which the laboratories works, analyzing the market information and numerical calculations were made to determine the operating costs of the laboratories, getting a financial plan with projections of cash flows that reflect the potential in its commercial functions. The realization of these plans is important for a competitive and strategic development of the laboratories. It presents aspects that strengthen and contribute to key activities such as strategic planning and marketing. In addition, these plans provide the necessary organizational and technical components to quantify in an accurate way the costs that both laboratories will incur in the sale of their services.
Trabajo Final de Graduación (Bachillerato en Administración de Empresas). Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2018.
Keywords: Oferta y demanda; Costos; Rentabilidad; Planeamiento estratégico; Negocios; Research Subject Categories::SOCIAL SCIENCES::Business and economics